Impact of Interpersonal Relations and Positioning on the Resolution of Conflicts in the EFL Classroom - Sitthirak, Chongrak (LEARN Journal: Language Education and Acquisition Research Network, 2022)
This article is based on the author’s doctoral thesis on the dynamics of interpersonal relations in the onsite classroom. Drawing on positioning theory (Davies & Harré, 1999; Harré, 2015), Sociocultural theory (Vygotsky, 1978; Lantolf & Thorne, 2007) and informed by the focus on interaction in Douglas Fir Group’s seminal paper (Douglas Fir Group (DFG), 2016), the research investigates how students position themselves and their classmates, the explanations for their choices, and how the dynamics of positioning and interpersonal relations affect their opportunities for language learning in group discussions. In this article, the researcher highlights the resolution of conflicts in different scenarios. The fluidity and overlap of positioning found in those interactions not only confirms the impact of interpersonal relations and positioning on resolving conflicts but also the provision and hindrance of students’ opportunities for language learning occurring across contexts and time.